Policy experiments in an agent-based model with credit networks - Tiziana Assenza; Alberto Cardaci; Domenico Delli Gatti; Jakob Grazzini (Kiel Institute for the World Economy (IfW), 2017)
In this paper the authors build upon Assenza et al. (Credit networks in the macroeconomics from the bottom-up model, 2015), which include firm-bank and bank-bank networks in the original macroeconomic model in Macroeconomics from the bottom-up (Delli Gatti et al., Macroeconomics from the Bottom-up, 2011). In particular, they extend that framework with the inclusion of a public sector and other modifications in order to carry out different policy experiments. More specifically, the authors test the implementation of a monetary policy by means of a standard Taylor rule, an unconventional monetary policy (i.e. cash in hands) and a set of macroprudential regulations. They explore the properties of the model for such different scenarios. Their results shed some light on the effectiveness of monetary and macroprudential policies in an economy with an interbank market during times of crises.
Keywords: C63; E51; E52; 330; Agent-based models; monetary policy; credit network